Alloying behavior and thermal stability of mechanically alloyed nano AlCoCrFeNiTi high-entropy alloy - Shivam V.; Shadangi Y.; Basu J.; Mukhopadhyay N.K. (My University, 2025)
In this investigation, we have reported the alloying behavior, phase evolution, and thermal stability of equiatomic AlCoCrFeNiTi high-entropy alloy (HEA). The 40 h milled powder shows good chemical homogeneity with agglomerated particles varying in the range of ∼3-18 μm. The formation of a nanostructured single-phase BCC (a = 2.85 ± 0.01 Å) was observed along with the minor tungsten carbide (WC) phase that formed due to contamination during milling. Thermal stability of the alloy has been studied using dynamic differential scanning calorimetry (DSC) thermogram and in situ X-ray diffraction. It has been found that this HEA is stable up to 600 °C (873 K). Consolidated samples at 1000 °C (1273 K) showed the transformation of body centered cubic (BCC) phase into the B2 (a = 2.87 ± 0.03 Å) phase co-existing with minor hexagonal WC (a = 2.90 Å, c = 2.83 Å) phase. Copyright © Materials Research Society 2019.